2010
DOI: 10.5565/rev/papers/v95n1.669
|View full text |Cite
|
Sign up to set email alerts
|

The effects of discrete contextual variables on «bullying» in the schoolyard

Abstract: In spite of the abundance of scientific literature that exists on bullying in schools, few studies have focused on the effects, both separate and combined, caused by contextual structural variables, such as geographical space, the municipal district, family, school, gender, male hegemonic culture, and exposure to the mass media. This article reviews to the present state of knowledge on the effects of these factors and provides empirical evidence of their influence on students aged between 12 and 16 in ESO (Obl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
1
0
0
Order By: Relevance
“…In that context, it was observed that living in the metropolitan region of Chile (where the largest capital of the country’s population is concentrated) is a risk factor for virtually all forms of PV, except for dating violence. Few studies have addressed this issue, but our findings coincide with seminal studies which identify structural variables, such as geographical area as a potential risk factor for peer violence (Hernández de Frutos et al, 2002). In that line, as suggested by theories from the sociological field, the metropolis ends up becoming relatively large, dense, and permanent settlements of areas formed by individuals of a homogeneous social, economic, and cultural levels, where the high density of inhabitants per square meter generates physical contact between people, but social relations tend to be distant and crystallize into segregation that causes a simple ascription of belonging to different groups, as well as interpersonal relations that do not generate loyalties or firm commitments, nor permanent bonds of self-help (Schwirian & Mesch, 1993).…”
Section: Discussionsupporting
confidence: 87%
“…In that context, it was observed that living in the metropolitan region of Chile (where the largest capital of the country’s population is concentrated) is a risk factor for virtually all forms of PV, except for dating violence. Few studies have addressed this issue, but our findings coincide with seminal studies which identify structural variables, such as geographical area as a potential risk factor for peer violence (Hernández de Frutos et al, 2002). In that line, as suggested by theories from the sociological field, the metropolis ends up becoming relatively large, dense, and permanent settlements of areas formed by individuals of a homogeneous social, economic, and cultural levels, where the high density of inhabitants per square meter generates physical contact between people, but social relations tend to be distant and crystallize into segregation that causes a simple ascription of belonging to different groups, as well as interpersonal relations that do not generate loyalties or firm commitments, nor permanent bonds of self-help (Schwirian & Mesch, 1993).…”
Section: Discussionsupporting
confidence: 87%